Assessing risk factors, mortality, and healthcare utilization associated with Clostridioides difficile infection in four Latin American countries - Yu,Holly (2021)
ABSTRACT Background: Clostridioides difficile infection (CDI) is the most common cause of healthcare-associated infections in Western countries. Risk factors, mortality, and healthcare utilization for CDI in Latin America are poorly understood. This study assessed risk factors and burden associated with nosocomial CDI in four Latin American countries. Methods: This retrospective, case-control study used databases and medical records from 8 hospitals in Argentina, Brazil, Chile, and Mexico to identify nosocomial CDI cases from 2014 − 2017. Cases were patients aged ≥18 years with diarrhea and a positive CDI test ≥72 h after hospital admission. Two controls (without diarrhea; length of hospital stay [LOS] ≥3 days; admitted ±14 days from case patient; shared same ward) were matched to each case. CDI-associated risk factors were assessed by univariate and multivariable analyses. CDI burden (LOS, in-hospital mortality) was compared between cases and controls. Results: The study included 481 cases and 962 controls. Mean age and sex were similar between cases and controls, but mean Charlson comorbidity index (4.3 vs 3.6; p< 0.001) and recent hospital admission (35.3% vs 18.8%; p< 0.001) were higher among cases. By multivariable analyses, CDI risk was associated with prior hospital admission within 3 months (odds ratio [OR], 2.08; 95% CI: 1.45, 2.97), recent antibiotic use (ie, carbapenem; OR, 2.85; 95% CI: 1.75, 4.64), acid suppressive therapy use (OR, 1.71; 95% CI: 1.14, 2.58), and medical conditions (ie, renal disease; OR, 1.48; 95% CI: 1.19, 1.85). In-hospital mortality rate (18.7% vs 6.9%; p< 0.001) and mean overall LOS (33.5 vs 18.8 days; p< 0.001) were higher and longer, respectively, in cases versus controls. Conclusion: Antibiotic exposure, preexisting medical conditions, and recent hospital admission were major risk factors for CDI in Argentina, Brazil, Chile, and Mexico. CDI was associated with increased in-hospital risk of death and longer LOS. These findings are consistent with published literature in Western countries.